Image guided percutaneous spine procedures using an optical see-through head mounted display: proof of concept and rationale. (30th May 2018) - Deib, Gerard; Johnson, Alex; Unberath, Mathias; Yu, Kevin; Andress, Sebastian; Qian, Long; Osgood, Gregory; Navab, Nassir; Hui, Ferdinand; Gailloud, Philippe
Abstract : Background and purpose: Optical see-through head mounted displays (OST-HMDs) offer a mixed reality (MixR) experience with unhindered procedural site visualization during procedures using high resolution radiographic imaging. This technical note describes our preliminary experience with percutaneous spine procedures utilizing OST-HMD as an alternative to traditional angiography suite monitors. Methods: MixR visualization was achieved using the Microsoft HoloLens system. Various spine procedures (vertebroplasty, kyphoplasty, and percutaneous discectomy) were performed on a lumbar spine phantom with commercially available devices. The HMD created a real time MixR environment by superimposing virtual posteroanterior and lateral views onto the interventionalist's field of view. The procedures were filmed from the operator's perspective. Videos were reviewed to assess whether key anatomic landmarks and materials were reliably visualized. Dosimetry and procedural times were recorded. The operator completed a questionnaire following each procedure, detailing benefits, limitations, and visualization mode preferences. Results: Percutaneous vertebroplasty, kyphoplasty, and discectomy procedures were successfully performed using OST-HMD image guidance on a lumbar spine phantom. Dosimetry and procedural time compared favorably with typical procedural times. Conventional and MixR visualization modes were equally effective in providing image guidance, with key anatomic landmarks and materials reliably visualized. Conclusion: This preliminary study demonstrates the feasibility of utilizing OST-HMDs for image guidance in interventional spine procedures. This novel visualization approach may serve as a valuable adjunct tool during minimally invasive percutaneous spine treatment.